2007
DOI: 10.1097/mbp.0b013e3280b083e2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of noninvasive oscillometric and intra-arterial blood pressure measurements in hyperacute stroke

Abstract: Noninvasive automatic oscillometric BP measurements underestimate direct SBP recordings and overestimate direct DBP readings in acute stroke. The magnitude of the discrepancy between intra-arterial and oscillometric SBP recordings is even more prominent in patients with critically elevated SBP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…14,24 Large variations between the indirect and direct blood pressure measurements have been well recognized. [25][26][27][28] A previous study assessing the accuracy of indirect blood pressure measurements at steady state clearly showed that the indirect methods underestimated SBP and overestimated DBP compared with the direct method, with s.d. of 10.5/7.6 mm Hg (SBP/DBP), 9.7/8.9 mm Hg and 8.1/6.5 mm Hg with the oscillometric method, microphone method and the auscultatory method, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…14,24 Large variations between the indirect and direct blood pressure measurements have been well recognized. [25][26][27][28] A previous study assessing the accuracy of indirect blood pressure measurements at steady state clearly showed that the indirect methods underestimated SBP and overestimated DBP compared with the direct method, with s.d. of 10.5/7.6 mm Hg (SBP/DBP), 9.7/8.9 mm Hg and 8.1/6.5 mm Hg with the oscillometric method, microphone method and the auscultatory method, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification as well as association to outcome changed significantly as a consequence of different calibrations. The change in amplification is explained by cuff specific under estimation of brachial systolic pressure by traditional pressure measurement methods, which is well known and has been reported over decades for both auscultatory and oscillometric measurements [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillometric devices (traditional upper extremity external BP cuffs) underestimate systolic, and overestimate diastolic, arterial pressure in many patients [19]. Arterial digital photoplethysmography and photoplethysmographic pulse oximetry need to be developed further before they are used for critical hemodynamic monitoring [20].…”
Section: Discussionmentioning
confidence: 99%